Peritumoral Immune Infiltrate as a Prognostic Biomarker in Thin Melanoma - Sabbatino, Francesco; Scognamiglio, Giosuè; Liguori, Luigi; Marra, Antonio; Anniciello, Anna Maria; Polcaro, Giovanna; Dal Col, Jessica; Caputo, Alessandro; Peluso, Anna Lucia; Botti, Gerardo; Zeppa, Pio; Ferrone, Soldano; et al. (Frontiers in Immunology, 2020)
Thin melanomas are tumors less than 1 mm thick according to Breslow classification. Their prognosis is in most cases excellent. However, a small subset of these tumors relapses. These clinical findings emphasize the need of novel prognostic biomarkers to identify this subset of tumors. Characterization of tumor immune microenvironment (TIME) is currently investigated as a prognostic and predictive biomarker for cancer immunotherapy in several solid tumors including melanoma. Here, taking into account the limited availability of tumor tissues, by characterizing some of the characteristics of TIME such as number of infiltrating lymphocytes, HLA class I antigen and PD-L1 expression, we show that number of infiltrating CD8+ and FOXP3+ T cells as well as CD8+/FOXP3+ T cell ratio can represent a useful prognostic biomarker in thin melanoma. Although further investigations in a larger patient cohort are needed, these findings have potential clinical significance since they can be used to define subgroups of thin melanoma patients who have a worse prognosis and might need different treatment modalities.